The geographical guide of Ptolemy of Alexandria - Roller, Duane W., author.
1 online resource.
Keywords: "This volume offers a detailed study of Ptolemy of Alexandria's Geographical Guide, whose eight books contain a wealth of geographical information unavailable elsewhere and represent the culmination of the Greco-Roman discipline of geography. Written near the middle of the second century AD, the Geographical Guide is the most anomalous of the surviving works of ancient geographical scholarship but offers a vivid record of the expansion of geographical knowledge in antiquity. Roller examines this peculiar text, which offers unique data about explorations in the far reaches of the inhabited world, from Thoule and Hibernia in the northwest to Kattigara in the southeast, and from Serike in northeastern Asia southwest into central Africa. He positions the Guide within the tradition of ancient geography and gives close attention to the reason why Ptolemy wrote the guide and how it contributes to the genre of geographical scholarship. There is also an emphasis on the topographic and ethnic material within the Guide that is new or unique, especially explorations in sub-Saharan Africa and knowledge of the world beyond India. As the Guide was written over half a century after the previous extant geographical work - the first books of Pliny's Natural History - the book also assesses how knowledge of geography changed during this period. This work is an essential text for students and scholars of ancient geography, and is also of interest to anyone working on the cultural history of the Roman Empire during this period"--